2014
DOI: 10.7309/jmtm.3.2.4
|View full text |Cite
|
Sign up to set email alerts
|

mHealth intervention development to support patients with active tuberculosis

Abstract: Background Mobile Health (mHealth) based interventions have been increasingly used to improve a broad range of health outcomes. However, few researchers have reported on the process or the application of theory to guide the development of mHealth based interventions, or specifically for tuberculosis (TB) treatment management. Aims To describe the steps, process, and considerations in developing a text messaging-based intervention to promote treatment adherence and provide support to patients with active TB. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…This is so in particular to sustain the existing DOT, reduced in reality from “daily” to “weekly” or even fewer directly observed strategies. These suggestions are an addition to this study [ 19 ] and highlights steps, processes and considerations to take into account in order to develop an SMS-based intervention for promoting adherence to TB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This is so in particular to sustain the existing DOT, reduced in reality from “daily” to “weekly” or even fewer directly observed strategies. These suggestions are an addition to this study [ 19 ] and highlights steps, processes and considerations to take into account in order to develop an SMS-based intervention for promoting adherence to TB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The TextTB intervention pilot study occurred from December 2011 through April 2013. Details of that study are reported elsewhere [ 30 , 34 ]. In brief, participants were randomized to the intervention group (TextTB, n=18) or control group (paper documentation, n=19) for the first 2 months of active TB treatment.…”
Section: Methodsmentioning
confidence: 99%
“…They received confirmation that their text messages were received, or they received query messages if they failed to send notifications. They also received twice weekly educational text messages that were based on the Information-Motivation-Behavior skills model [ 34 - 36 ]. The team members were the study principal investigator (PI), a regional TB director/pulmonologist, the lead regional TB social worker, a regional TB staff member, two TB-specialized clinic registered nurses (RNs), and the hospital TB program director/pulmonologist.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, we utilized a multidisciplinary research team to design and test the GEM tool and intervention. Thus, although the GEM intervention was developed at a single site, we believe that the diverse training and perspectives of our team were key to developing a complex intervention that is widely applicable and has the potential to be implemented and easily tailored to other VA sites and other healthcare settings more broadly [ 83 , 84 ].…”
Section: Limitationsmentioning
confidence: 99%